Mechanical Design of a Spatial Mechanism for the Robot Head Configuration in Social Robotics - Alvarez, Jorge (2020)
The manuscript presents the mechanical design of the head configuration in the Human Robot Interaction (HRI) used for the message transmission of emotions through nonverbal communications styles. The evolution of this structure results on a natural movement reproduction for the implementation of non-verbal communication strategies in a normal behavior, achieve the main patterns to evaluate the social interaction with the robotic platform. The mechanical design result from a biomechanical evaluation of the Pitch, Roll, and Yaw trajectories of the human head and neck. The spatial mechanisms, according to the Grübber formula for Spatial Robots, allows 4 degrees of freedom. The spatial chain has universal, prismatic, spiral and revolute joins of the mechanical model-ling. This CAD model permit the 3D print of cardan elements to performance the structure of the mechanisms. The appearance is friendly and the interface reach similar capabilities than a human would have for communication. Finally, human interaction through the head movement gives the opportunity in the future for the evaluation of more parameters of the social robotic interaction between robots-humans and robots-robots. © Springer Nature Switzerland AG 2020.